The role of cognitive function and physical activity in physical decline in older adults across the cognitive spectrum - Morag E. Taylor (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Objectives: The aim of this study was to investigate physical decline over 1-year in a cohort of older people across the cognitive spectrum. Methods: Physical function was assessed using the Physiological Profile Assessment (PPA) in 593 participants (cognitively normal [CN]: n = 342, mild cognitive impairment [MCI]: n = 77, dementia: n = 174) at baseline and in 490 participants available for reassessment 1-year later. Neuropsychological performance and physical activity (PA) were assessed at baseline. Results: Median baseline PPA scores for CN, MCI and dementia groups were 0.41 (IQR = −0.09–1.02), 0.66 (IQR = −0.06–1.15) and 2.37 (IQR = 0.93–3.78) respectively. All baseline neuropsychological domains and PA were significantly associated with baseline PPA. There were significant interaction terms (Time × Cognitive Group, Global Cognition, Processing Speed, Executive Function and PA) in the models investigating PPA decline. In multivariate analysis the Time × Executive Function and PA interaction terms were significant, indicating that participants with poorer baseline executive function and reduced PA demonstrated greater physical decline when compared to individuals with better executive function and PA respectively. Discussion: Having MCI or dementia is associated with greater physical decline compared to CN older people. Physical inactivity and executive dysfunction were associated with physical decline in this sample, which included participants with MCI and dementia. Both factors influencing physical decline are potentially amenable to interventions e.g. exercise.